Repetition and Its Effect in Salman Kuvli S Poems - Abdulkarim, Abdulqader N. (Humanities Journal of University of Zakho, 2018)
Complex phenomenon of repetition stylistic connotations, suggestions deep, hardly confine their meaning, so it was this research is an attempt to clarify this phenomenon and follow-up in the poetry (Salman covly). At first, we stopped on the concept of redundancy in terms of idiomatic language and then we stopped at different critics and contrast their views, and then when some types of repetition (at the level of repetition of sounds and words and phrases and then to repeat the moral connotations) in the hair.